Effect of Cross-Linking with Ginger and Garlic on the Properties of Cassava Starch - Jandrajupalli, Sudhakararao; R, Paraimalavalli (JOURNAL OF ROOT CROPS, 2015)
Cross-linking is a type of chemical modification to improve granule stability with new covalent bonds, thus providing desired functional properties. The present study was undertaken to modify cassava starch with active components of ginger and garlic and to determine the properties of modified cassava starch. The cassava starch was modified with 5% ginger (A), 10% ginger (B), 5% garlic (C) and 10% garlic (D). The degree of cross-linking was determined from the viscosity values and chemical and functional properties of all cross-linked starches were analyzed by standard methods. Results of the study showed that higher concentrations of ginger and garlic increased the degree of cross-linking. Native cassava starch had higher protein content (0.6 ±0.09%) than cross-linked cassava starches (0.11 ±0.02-0.57 ±0.01%), amylose content was higher in cross-linked starch (22.7 ±0.52- 27.2 ±0.19%) than native starch (23.2 ±1.20%). Water and oil absorption capacities were not significantly different between native (0.96 ±0.01 g g-1) and cross-linked starches (0.87 ±0.03 - 0.93 ±0.04 g g-1). Cross-linked starch had higher swelling power (14.5 ±0.45-14.8 ±0.36 g g-1) and solubility (8.1 ±0.42-9.0 ±1.36%) when compared to those of native starch (11.1 ±0.84 g g-1 and 7.1 ±0.62%, respectively). Lower viscous properties were observed for cross-linked (1975.00 - 2565.00 cP) starch than that of native starch (3733.66 cP). Cassava starch could be modified with ginger and garlic and distinctive properties were exhibited by the cross-linked starches.